2020
DOI: 10.5267/j.msl.2020.2.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality management in business: Evidence in Vietnam manufacturing and technology enterprises

Abstract: This paper aimed to evaluate the factors affecting quality management (QM) through the quality management system according to ISO 9001 standards of Vietnam businesses. The authors surveyed on 200 manufacturing and technology enterprises that apply ISO 9001 quality management in Hanoi and Da Nang and HCMC. Factors affecting the effectiveness of quality management under ISO 9001 include five elements: (1) Management commitment; (2) Staff involvement; (3) Cooperation of customers and suppliers; (4) Consultants; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Talking about the managerial implications, our results show that the implementation of ISO 9001 and ISO 14001 standards is a wise strategic choice, because the implementation of their requirements allows companies not only to reduce the negative impact on the environment, but also to improve important aspects of the functioning of supply chains. As the observed benefits are independent of the country, it can be concluded that standardized management systems are a universal solution recommended for most organizations and also facilitate long-term relationships with companies that apply similar standards (Xuan and Trung, 2020). However, it should be emphasized that large organizations gain greater benefits from the implementation of the studied management standards.…”
Section: Discussionmentioning
confidence: 99%
“…Talking about the managerial implications, our results show that the implementation of ISO 9001 and ISO 14001 standards is a wise strategic choice, because the implementation of their requirements allows companies not only to reduce the negative impact on the environment, but also to improve important aspects of the functioning of supply chains. As the observed benefits are independent of the country, it can be concluded that standardized management systems are a universal solution recommended for most organizations and also facilitate long-term relationships with companies that apply similar standards (Xuan and Trung, 2020). However, it should be emphasized that large organizations gain greater benefits from the implementation of the studied management standards.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous businesses assert that by implementing ISO 9001 standards, they were able to reduce costs, boost customer satisfaction, and streamline procedures. An organization's possession of an ISO 9001 certificate reveals the following: the business adheres to the requirements outlined in the ISO 9001 standard for production and meets business requirements; the product satisfies the needs of the customer the business listed [17].…”
Section: Total Quality Managementmentioning
confidence: 99%